A paleoceanographic approach of MIS5e interglacial deposits at the western margin of Cyclades plateau - Ratopoulou, M.; Rousakis, G.; Triantaphyllou, M.; Gogou, A.; Bouloubassi, I.; Dimiza, M.; Parinos, C.; Lykousis, V. (11th Panhellenic Symposium on Oceanography and Fisheries, 2015)
Paleoceanographic proxies, such as marine micropaleontology, sedimentology and organic geochemistry have been performed in the sediment record of SK-3 gravity core (total length 217cm, water depth 249m) in order to provide possible determination of late interglacial-Holocene the paleoenvironmental changes, at the south western margin of Cyclades plateau in the SW Aegean Sea. The sediment core exhibits two sapropels layer; the first one is associated with sapropel S1. The second sapropelic layer which we focus on represents anoxic conditions during the high sea-level warm event associated with sapropel S5 deposition.